Transceiver Optimization for Interference MIMO Relay Communication Systems - Nguyen, Khoa Xuan (Curtin University, 2017)
This thesis focuses on transceivers design for interference MIMO relay systems. Based on the MMSE criterion, several iterative algorithms are proposed to jointly optimize the source, relay, and receiver matrices subjecting to the individual power constraints at the source and the relay nodes. These algorithms have better performance than some existing algorithms and provide a better performance-complexity trade-off which is interesting in practical interference MIMO relay communication systems.